2002
DOI: 10.17221/6114-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity in 19 Glycine max (L.) Merr. accessions included in the Czech National Collection of soybean genotypes

Abstract: Abstract:The random amplified polymorphic DNA (RAPD) technique was used to evaluate both genetic diversity among 19 soybean accessions included in the Czech National Collection of Soybean Genotypes and their potential as a new source of genetic variations for soybean breeding programs. Only 22 of all the 40 random primers used in RAPD reactions showed polymorphism acceptable for an effective characterisation of these accessions. Altogether 122 highly reproducible RAPD fragments were generated, 55 of them were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…Forty-six polymorphic bands (43%) were identified with 21 RAPD primers in this study. Similar results were shown by BARANEK et al, (2002), who detected 122 highly reproducible fragments with 22 RAPD primers, and 55 of them were polymorphic (46%). As compared to the results of other authors, polymorphism found in our study had reached slightly higher values.…”
Section: Rapd Datasupporting
confidence: 83%
“…Forty-six polymorphic bands (43%) were identified with 21 RAPD primers in this study. Similar results were shown by BARANEK et al, (2002), who detected 122 highly reproducible fragments with 22 RAPD primers, and 55 of them were polymorphic (46%). As compared to the results of other authors, polymorphism found in our study had reached slightly higher values.…”
Section: Rapd Datasupporting
confidence: 83%
“…The use of RAPDs for analyzing soybean genome was started in the early 1990s. The RAPD markers have been widely used for genetic diversity study of soybean germplasm (Correa et al, 1999;Baranek et al, 2002;Nikolic et al, 2007;Peric et al, 2008a) (Fig. 3.).…”
Section: Randomly Amplified Polymorphic Dnamentioning
confidence: 99%
“…Molecular markers are known as one of the best approaches to study genetic material as well as to assess genetic variation in crop gene pools (Badr, 2008;Mondini et al, 2009;Wang et al, 2016). A number of PCR based molecular markers such as Random Amplified Polymorphic DNA (RAPD), Inter Simple Sequence Repeats (ISSR) and Amplified Fragment Length Polymporhism (AFLP) have been used to assess genetic variability and cultivar identification in soybean (Barakat, 2004;Baránek et al, 2002;Chowdhury et al, 2001;El-Kholy, 2013) and other plant populations (Hoque and Hasan, 2012;Lin et al, 2009). RAPD is often used successfully to assess genetic diversity among species as it is fast, less technical and expensive and may reveal dominant molecular marker of good potential (Badr et al, 2012;Prasanthi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%